Contingent valuation of Taguibo watershed in Butuan City through willingness to pay method - Peñaflor, Jan Kendrick B. (2017)
Water is important for human survival but there is limited amount of water accessible and share among 7.3 billion humans around the world. Butuan City Water District (BCWD) is a utility facility that controls and supplies water from Taguibo Watershed to the households and commercial businesses in Butuan City. As a part of the water conservation effort of BCWD, protection and rehabilitation activities to preserve the watershed were initiated. BCWD has conceptualized a watershed management program to improve the condition of Taguibo watershed and minimize water service interruptions. As such, this research aims to estimate the Butuan households? willingness to pay for the Watershed Management Program through probit regression. Using a household survey instrument, 350 respondents from different barangays in Butuan City were interviewed and data on WTP was elicited following a dichotomous referendum format. Household water conservation effort and environmental literacy were also obtained and analyzed. Results show that Butuanons have low watershed awareness and environmental literacy. Watershed awareness and educational attainment were among the factor that increases the likelihood of the households to pay for the watershed management program. Using the result of the probits model, the estimated mean WTP of Butuanons is P/ 34.23. These findings suggest 2 practical insights: (1) promote educational programs and campaigns that are geared towards promoting household water conservation practices, and increasing environmental and watershed awareness, (2) consider the estimated WTP in the implementation of the watershed rehabilitation program.